168 Case Report – Hungry for the optimal regime: a patient-designed method to withdraw artificial feeding at the end of life. (14th March 2023) - Russell, Amy; Curtis, Matthew
Abstract : Background: There is currently no defined approach for altering feed volume to withdraw artificial feeding when a patient with neurological disease requests it, at the end of their life. Aims: We present a patient-designed regime used to withdraw artificial feeding in the community, without the patient experiencing distressing symptoms of hunger, enabling peaceful death at home. Case Study Description: A 58 year old man with Motor Neurone Disease chose to stop artificial feeding when his communication and movement were severely limited. The patient decided they no longer had quality of life and wanted to withdraw feed to allow natural death. At this stage they were receiving 1000mls of feed via PEG tube within 24 hours. The patient's main concern was to avoid developing hunger and related pains. They chose to reduce their feed in 250ml per week stages, over a 4-week period. Their reasoning was due to a previous positive experience of reduction of feed by 250mls for symptom management of secretions. The patient felt this would be the least symptomatic approach to withdrawal. Results: No hunger was experienced during staged withdrawal. At the point when feed and fluids were stopped completely, the patient experienced some mild, intermittent hunger but was not distressed by it. Nausea and secretions occurred and were addressed with standard palliative approaches. Conclusion: This approach was effective for this patient, who only experienced mild symptoms of hunger; however, we cannot be certain it would be effective in all situations. There is currently no recognised guidance for withdrawal of artificial feeding in these circumstances. Given the relative infrequency of these cases, research on a large scale would allow collation of data to devise and develop the optimal regime. We feel it is important this can be facilitated in a patients' home as well as in healthcare settings.